Derivations and automor phisms of locally matrix algebras and groups - Bezushchak, O.O. (Доповіді НАН України, 2020)
We describe derivations and automorphisms of infinite tensor products of matrix algebras. Using this description, we show that, for a countable–dimensional locally matrix algebra A over a field F, the dimension of the Lie algebra of outer derivations of A and the order of the group of outer automorphisms of A are both equal to |F|ᵡ₀, where |F| is the cardinality of the field F. Let A* be the group of invertible elements of a unital locally matrix algebra A. We describe isomorphisms of groups [A*, A*]. In particular, we show that inductive limits of groups SLn(F) are determined by their Steinitz numbers. Описано диференцiювання та автоморфiзми нескiнченних тензорних добуткiв матричних алгебр. З використанням цього опису показано, що для злiченновимiрної локально матричної алгебри A над полем F розмiрностi алгебри Лi зовнiшнiх диференцiювань A i порядок групи зовнiшнiх автоморфiзмiв A збiгаються i дорiвнюють |F|ᵡ₀, де |F| означає потужнiсть поля F. Нехай A* — група оборотних елементiв унiтальної локально матричної алгебри A. Описано iзо морфiзми групи [A*, A*]. Зокрема, показано, що iндуктивнi границi груп SLn(F) визначаються їх числами Стейнiца.